ANALYSIS OF WATER AVAILABILITY IN CEMPAKA RESERVOIR AND GUNUNG KUPANG RESERVOIR FOR FLOOD CONTROL IN CEMPAKA DISTRICT BANJARBARU CITY - Danianty, Rahma; Novitasari, Novitasari; Sofia, Elma (Universitas Lambung Mangkurat, 2025)
During the rainy season, the Cempaka District in Banjarbaru City frequently experiences flooding. One of the government's efforts to mitigate flooding is the construction of reservoirs in the upstream area of Cempaka District, namely the Cempaka Reservoir and the Gunung Kupang Reservoir. Therefore, it is essential to conduct a study on the water availability in these reservoirs. The results of the water availability analysis show that the highest discharge for the Cempaka Reservoir is 1,032 m³/s, while the Gunung Kupang Reservoir records 0,378 m³/s. The largest dependable discharge is 1,07 m³/s for the Cempaka Reservoir and 0,39 m³/s for the Gunung Kupang Reservoir. Keywords: Water Availability, Dependable Discharge, Cempaka Reservoir, Gunung Kupang Reservoir